Perencanaan Jalur Interpretasi Alam Menggunakan Sistem Informasi Geografis - Tri Satyatama; EKS Harini Muntasib; Lilik Budi Prasetyo (Jurnal Manajemen Hutan Tropika, 2010)
Being established in 2004, Gunung Merbabu National Park (GMNP) is one among several new national parks in Indonesia. Ecotourism activities in this area have not been properly developed by Perum Perhutani (as the past management authority) although the area is very potential to be developed as an ecotourism site for activities such as nature interpretation, apart from camping and hiking which are already carried out. With the change of the area’s status into a national park, the opportunity of ecotourism development is increased as the area is presently managed by a management authority named Gunung Merbabu National Park Office. As a part of ecotourism, nature interpretation is very important in connecting visitors to natural resources, which is one of the urgent services of GMNP. The objective of this research is to develop interpretation planning of various nature tracks in the park, based on the tracks’ resources and users’ demands. The Query Builder tool was employed in the selection of the user-oriented nature interpretation tracks. The synthesis of tracks’ resources and users’ demand resulted in 8 tracks, e.g. Selo–Puncak, Tekelan–Puncak, Selo II, Selo III, Tekelan IV, TWA–Krinjingan Waterfall, TWA–Watu Tadah Waterfal, and TWA–”Dufan”.